Molecular classification and therapeutics in diffuse large B-cell lymphoma - Shimkus, Gaelen; Nonaka, Taichiro (Frontiers in Molecular Biosciences, 2023)
DLBCL encompasses a wide variety of disease states that have to date been sub-grouped and characterized based on immunohistochemical methods, which provide limited prognostic value to clinicians and no alteration in treatment regimen. The addition of rituximab to CHOP therapy was the last leap forward in terms of treatment, but regimens currently follow a standardized course when disease becomes refractory with no individualization based on genotype. Research groups are tentatively proposing new strategies for categorizing DLBCL based on genetic abnormalities that are frequently found together to better predict disease course following dysregulation of specific pathways and to deliver targeted treatment. Novel algorithms in combination with next generation sequencing techniques have identified between 4 and 7 subgroups of DLBCL, depending on the research team, with potentially significant and actionable genetic alterations. Various drugs aimed at pathways including BCR signaling, NF-κB dysfunction, and epigenetic regulation have shown promise in their respective groups and may show initial utility as second or third line therapies to patients with recurrent DLBCL. Implementation of subgroups will allow collection of necessary data to determine which groups are significant, which treatments may be indicated, and will provide better insight to clinicians and patients on specific disease course.